INFLUENCE OF ECONOMIC VALUE AND FUNDAMENTAL ANALYSIS TOWARD STOCK MARKET (STUDIES ON THE RETAIL TRADE INDUSTRY SECTOR) - Widyatmini Widyatmini; Michael Valentino Damanik (Universitas Gunadarma, 2009)
The objective of this research is to measure the influence of economics value added and fundamental analysis toward stock price on retail industry. Data which was deployed on this research are company financial report and stock price. Further, data was analyzed using regression method by deploying SPSS software. Research result shows that all independent variables proposed (economics value added, current ratio, quick ratio, total asset turnover ratio, inventory turnover ratio, gross profit margin ratio, net profit margin ratio, return on asset ratio, return on equity ratio, debt ratio, debt equity ratio, leverage ratio, earning per share, and price earnings ratio) influence stock price. But partially, only net profit margin ratio and earnings per share influence stock price significantly.Key words: stock price, economic value added, and fundamental analysis